Small molecules as pro-apoptotic anticancer agents. (September 2012) - Seneci, Pierfausto
The quest for potent and selective targeted therapies in anticancer research is taking advantage of apoptosis-related mechanisms of action to identify a number of novel clinical candidates. This review is chemically focused on small molecules and deals with five target families that influence caspase-dependent apoptosis: caspase-3, Bcl-2 and IAP protein family members, p53 and the proteasome. Each target class is briefly described at first in terms of its involvement and relevance in tumor initiation and progression. Drug candidates currently undergoing clinical trials are then presented for each target class, followed by a quick summary of target-modulating chemotypes that have appeared in patent literature since 2006. Finally, future trends likely to become significant in apoptosis-targeted cancer therapies are presented and discussed.